Erythrocyte-binding assays reveal higher binding of Plasmodium knowlesi Duffy binding protein to human Fya+/b+ erythrocytes than to Fya+/b- erythrocytes - Fong, Mun Yik; Cheong, Fei Wen; Lau, Yee Ling (BMC, 2018)
BACKGROUND: The merozoite of the zoonotic Plasmodium knowlesi invades human erythrocytes via the binding of its Duffy binding protein (PkDBPαII) to the Duffy antigen on the eythrocytes. The Duffy antigen has two immunologically distinct forms, Fya and Fyb. In this study, the erythrocyte-binding assay was used to quantitatively determine and compare the binding level of PkDBPαII to Fya+/b+ and Fya+/b- human erythrocytes. RESULTS: In the erythrocyte-binding assay, binding level was determined by scoring the number of rosettes that were formed by erythrocytes surrounding transfected mammalian COS-7 cells which expressed PkDBPαII. The assay result revealed a significant difference in the binding level. The number of rosettes scored for Fya+/b+ was 1.64-fold higher than that of Fya+/b- (155.50 ± 34.32 and 94.75 ± 23.16 rosettes, respectively; t(6) = -2.935, P = 0.026). CONCLUSIONS: The erythrocyte-binding assay provided a simple approach to quantitatively determine the binding level of PkDBPαII to the erythrocyte Duffy antigen. Using this assay, PkDBPαII was found to display higher binding to Fya+/b+ erythrocytes than to Fya+/b- erythrocytes.